Literatur review: Manajemen Talenta pada Pengembangan Sumber Daya Manusia Di Era Digital - Manan, Irma Rohmatul; Gunawan, Ahmad (Universitas Pahlawan Tuanku Tambusai, 2023)
Globalization around the world has entered the digital era, where digitalization is a key factor in organizational life. In recent years, there has been a steady increase in the use of technology in human resource (HR) strategy and planning. This article discusses the application of talent management to develop human resources in the digital era. The literature review method used in writing this article, involves searching databases from various reference sources such as journals, books, and data related to talent management. Effective talent management involves not only traditional human resource management, but also focuses efforts on developing digital skills, identifying suitable talent with digital initiatives, and creating a culture of innovation. Key aspects of successful talent management in the digital age include flexibility, assigning greater responsibility to employees, and mobility. The use of technology also plays a key role in talent management, with tools and data analytics supporting better decision making. Regular evaluations and employee engagement are important aspects of ensuring successful talent management. Effective talent management will help companies stay competitive and ready for evolving technological changes.